2002
DOI: 10.1083/jcb.200207050
|View full text |Cite
|
Sign up to set email alerts
|

Distinct claudins and associated PDZ proteins form different autotypic tight junctions in myelinating Schwann cells

Abstract: The apposed membranes of myelinating Schwann cells are joined by several types of junctional specializations known as autotypic or reflexive junctions. These include tight, gap, and adherens junctions, all of which are found in regions of noncompact myelin: the paranodal loops, incisures of Schmidt-Lanterman, and mesaxons. The molecular components of autotypic tight junctions have not been established. Here we report that two homologues of Discs Lost–multi PDZ domain protein (MUPP)1, and Pals-associated tight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
171
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(182 citation statements)
references
References 72 publications
8
171
2
1
Order By: Relevance
“…Our original identification of MBEC1/claudin-5 mRNA and protein expression by the endothelial cells of the BBB (8) has subsequently been confirmed by others (34,41,42). In addition to BBB and other endothelial cells, our studies (8) and those of others (32,35,45,56) have revealed claudin-5 expression in epithelial cells as well as other specialized cell types, including pancreatic acinar cells (45) and myelinating Schwann cells in nerves (44).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Our original identification of MBEC1/claudin-5 mRNA and protein expression by the endothelial cells of the BBB (8) has subsequently been confirmed by others (34,41,42). In addition to BBB and other endothelial cells, our studies (8) and those of others (32,35,45,56) have revealed claudin-5 expression in epithelial cells as well as other specialized cell types, including pancreatic acinar cells (45) and myelinating Schwann cells in nerves (44).…”
Section: Discussionmentioning
confidence: 52%
“…The primer pairs for substitution of Cys 64 with Ser were 5Ј-ACCGGGCACATGCAGTCCAAGGTGTATGAATCT-3Ј and 5Ј-AGATTCATACACCTTGGACTGCATGTGCCCGGT-3Ј. The primer pairs for substitution of the Gln 44 residue with Asn were 5Ј-CAACATCGTGA CGGCGAACACGACTTGGAAGGGGC-3Ј and 5Ј-GCCCCTTCCAAGTCGT GTTCGCCGTCACGATGTTG-3Ј. The primer pairs for replacement of Leu 50 and Trp 51 with Gln and Arg, respectively, were 5Ј-ACGACTTGGAAGGGGC AAAGGATGTCGTGCGTGGT-3Ј and 5Ј-ACCACGCACGACATCCTTTGC CCCTTCCAAGTCGT-3Ј.…”
Section: Methodsmentioning
confidence: 99%
“…Typically thought of as a component of compact myelin (Haney et al, 1996), PMP22 has not yet been localized to tight junctions of PNS myelin. Based on the effects of PMP22 on epithelial paracellular permeability, the protein could have a similar role in PNS myelin at claudin-1-and -5-positive autotypic tight junctions (Poliak et al, 2002). Therefore, modulating PMP22 in an epithelial model may provide some clues as to the function of the protein in PNS myelin.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, myelin sheath structural proteins, such as Claudin 5 and Mupp1 (16), which interact with each other in the Schmidt-Lanterman incisures, were present in the DEC ALL data set. These results encouraged us to perform quantitative RT-PCR analysis to examine the expression of other DEC ALL genes, including EphB6, p21, Pea15, Nr4a2, and the potassium ion channel KcnK1 in immature cultured Schwann cells, and in developing and injured nerves.…”
Section: Myelination-associated Genes Are Enriched In the Egr2mentioning
confidence: 99%